Zero kara hajimeru dēta saiensu Python de manabu kihon to jissen - Grus, Joel (Orairī Japan, 2020)
"Data science libraries, frameworks, modules, and toolkits are great for doing data science, but they're also a good way to dive into the discipline without actually understanding data science. In this book, you'll learn how many of the most fundamental data science tools and algorithms work by implementing them from scratch. If you have an aptitude for mathematics and some programming skills, author Joel Grus will help you get comfortable with the math and statistics at the core of data science, and with hacking skills you need to get started as a data scientist. Today's messy glut of data holds answers to questions no one's even thought to ask. This book provides you with the know-how to dig those answers out. Get a crash course in Python Learn the basics of linear algebra, statistics, and probability--and understand how and when they're used in data science Collect, explore, clean, munge, and manipulate data Dive into the fundamentals of machine learning Implement models such as k-nearest Neighbors, Naive Bayes, linear and logistic regression, decision trees, neural networks, and clustering Explore recommender systems, natural language processing, network analysis, MapReduce, and databases." --
Includes index. - Online resource; title from title details screen (O'Reilly, viewed April 20, 2022)
Keywords: Data mining -- Statistical methods; Mathematical statistics; Database management; Data structures (Computer science); Python (Computer program language); Bases de données; Gestion; Structures de données (Informatique); Python (Langage de programmation); Data mining; Statistical methods